2020
DOI: 10.26452/ijrps.v11ispl1.1973
|View full text |Cite
|
Sign up to set email alerts
|

Role of GS-5734 (Remdesivir) in inhibiting SARS-CoV and MERS-CoV: The expected role of GS-5734 (Remdesivir) in COVID-19 (2019-nCoV) - VYTR hypothesis.

Abstract: Coronaviruses (CoVs) are enveloped RNA viruses related to the family Coronaviridae, the order Nirdovales, and observed in humans and other mammals. In December 2019, many pneumonia cases reported by patients with unknown causes, mainly associated with seafood and wet animal market in Wuhan, China, and where clinically resembled viral pneumonia. At present, there is no existence of antiviral drugs for the treatment of CoV infections. The results of our study are GS-5734 strongly inhibits SARS-CoV and MERS-CoV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Remdesivir was originally developed to combat Ebola and related viruses; it works by inhibiting RNA-dependent RNA polymerase [37]. Since the target is similar, both in vitro and in vivo experiments showed that the drug can inhibit the coronaviruses that cause SARS and MERS [38]. The first COVID-19 patient from Washington, U.S. was given remdesivir when his condition worsened, and the case report suggests that his condition improved [39].…”
Section: Remdesivirmentioning
confidence: 99%
“…Remdesivir was originally developed to combat Ebola and related viruses; it works by inhibiting RNA-dependent RNA polymerase [37]. Since the target is similar, both in vitro and in vivo experiments showed that the drug can inhibit the coronaviruses that cause SARS and MERS [38]. The first COVID-19 patient from Washington, U.S. was given remdesivir when his condition worsened, and the case report suggests that his condition improved [39].…”
Section: Remdesivirmentioning
confidence: 99%
“…Wang et al reported that the mechanism of action of remdesivir depends on blocking SARS-CoV-2 infection at low concentrations with a high selectivity index [26]. Although remdesivir (GS-5734) still needs clinical studies to prove its efficiency against COVID-19 but according to its broad-spectrum properties, it is expected to inhibit COVID-19 as it was a potential antiviral drug to treat other CoVs infections [27]. On the 5th of February, 2020, clinical studies on remdesivir in China were started using randomized placebo-controlled, double-blind, multicenter clinical trial.…”
Section: Remdesivirmentioning
confidence: 99%
“…[39] This may be due to the absence of Exonmediated proofreading in viruses sensitive to Remdesivir. [40] One of the first trials of Remdesivir was performed by the Gilead sciences center in hospitalized patients with confirmed SARS-CoV-2 having oxygen saturation < 94% or a need for oxygen support. Till 28 days of follow-up, the cumulative incidence of clinical improvement was 84% (95% CI 70-99) by Kaplan-Meier analysis and it was less among patients receiving invasive ventilation compared to non-invasive ventilation.…”
Section: Remdesivirmentioning
confidence: 99%